An Analysis of the Application of Performance Appraisal in Enterprise Human Resource Management - Su, Kaiwei (Transactions on Economics, Business and Management Research, 2024)
As competition in society intensifies, modern enterprises must recognize the value of human resource management to meet the demands of ongoing development. Performance appraisal, as a vital tool in human resource management, cannot be overlooked. It not only accurately assesses employee performance but also provides a scientific basis for HR decision-making, motivating employees to actively engage in their work and spurring team innovation. Therefore, in practical application, performance appraisal should set assessment goals scientifically and ensure the fairness and reasonableness of the results. Simultaneously, attention must be paid to the feedback mechanism of performance appraisal, regularly interacting with employees to help them recognize their shortcomings and improve, thus fully leveraging the value of human resources to support the long-term development of the enterprise.